Rate of decomposition of leaflitter in an age series gmelina arborea robx plantation in a Nigerian lowland rain forest (2011)
The study was carried out to investigate the rate of decomposition of Gmelina arborea Robx leaflitter in an age series in Gmelina plantation in shasa forest reserve in a Nigerian low land Forest. Rate of decomposition of Gmelina leaf litter was determined using litter bag technique and mass balance analysis to quantify the rate of leaf litter decay in the stands. Data collected were analyzed using descriptive and inferential statistics at 0.05 level of significance. Nitrogen(N) and Phosphorus(P) were significantly different among the three stand ages (p <0.05). A fast decomposing rate of the leaves relatively increases P after mineralization. Nitrogen, Phosphorus, Calcium and Magnesium decreased significantly with soil depth, while Potassium and PH showed no significant association with soil depth. There was a decrease in sand and silt percentages with increasing depth. Clay content however increased with increasing soil depth (P<0.05). Decomposition constant (K) of 0.08 was found for the leaves, with a turnover time of 3 to 6 months. Macro nutrients concentration in the leaf litter decrease in the order Ca> N> Mg> P> K. The study revealed that the rate of decomposition is very fast in the studied site.